EFFECT OF VARIOUS ORGANIC NUTRIENTS ON GROWTH, BIOMASS YIELD AND HYDROCARBON PRODUCTION OF EUPHORBIA LATHYRIS L., A HYDROCARBON YIELDING PLANT: Life Sciences-Botany - JOLLY GARG; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2012)
Energy security is one of the most pressing challenges of the 21st century. A shift to next-generational fuels and increased use of renewable source of energy are increasingly being considered as viable options. Euphorbia lathyris L. is one of the most-suitable species that falls into the category of hydrocarbon yielding plants. This plant is suitable to grow in arid and semiarid climate. Maximum increase in above ground fresh weight and dry weight, per cent dry weight; hexane extractables, methanol extractables, total hydrocarbon extractables (hexane extractables and methanol extractables); chlorophyll a, chlorophyll b and total chlorophyll contents were recorded at 14,000 kg/ha of farm yard manure. Maximum under- ground fresh and dry weights, under-ground percent dry weight; chlorophyll b, total chlorophyll; hexane, methanol and total hydrocarbon contents were maximum at 14,000 kg/ha of compost.